Islamic Educations Learning Environment at Al-Ihsan Integrated Islamic Elementary School Banjarmasin - Amalia Fitriani (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
he Islamic Religious Education learning environment is a foundation of values ​​in instilling religious attitudes. The formation of religious attitudes can take place in various environments, namely in the informal family education environment, in the formal school education environment, and in the non-formal community education environment. This study aims to analyze the Islamic Religious Education learning environment at SDIT A-lhsan Banjarmasin. Researchers used Qualitative methods with data collection techniques, namely collecting data through observation, interviews and documentation. The results of this study are: The results of this study are that there are several problems from educators and students. From students, namely: some of the students have difficulty understanding the learning material. students have difficulty pronouncing the hijaiyyah letters properly and correctly. some students still have not fully memorized the surah readings. And from educators, namely educators have difficulty understanding the characteristics of students. educators have difficulty in conveying learning materials to students, educators do not feel difficulty in determining methods for each lesson. limited learning media, the learning media provided are quite adequate such as whiteboards, stationery equipment, LCD. Implementation of learning evaluation, evaluation is carried out at the end of the lesson.